Estimating the potential of rain-fed agriculture - Droogers, Peter; Seckler, David; Makin, Ian W. (International Water Management Institute, 2001)
A global estimate of the potential for rain-fed agriculture could provide an answer to the question "How much irrigation is required?" Global studies done to date have relied on course resolution climate data (0.5-1 degree arc). In this study a high-resolution climate dataset (10-minute arc) was combined with a soil water storage capacity map and a dynamic water and crop model to estimate the potential for rain-fed agriculture. The methodology applied here, based ona high-resolution climate dataset, allows analyses on a global scale without losing the smaller regional-scale issues.